Adapting psychological therapies for autism. (January 2018) - Cooper, K.; Loades, M.E.; Russell, A.
Highlights: Adapted CBT can be an effective intervention for mental health problems in autism. We surveyed therapist confidence and skills in adapting CBT for autistic people. Therapists varied in confidence across skills and did make some adaptations. Therapists reported challenges to working with this group. Well-designed training and supervision is required. Abstract: Background: Psychological interventions informed by cognitive behavioural theory have proven efficacy in treating mild-moderate anxiety and depression. They have been successfully adapted for autistic children and adults who experience disproportionately high rates of co-occurring emotional problems. There has been little research into the perspectives and experience of psychological therapists adapting cognitive behavioural therapy (CBT) as part of routine clinical practice. We surveyed therapist skills, experience and confidence in working psychologically with autistic people, in order to highlight gaps and needs, as well as strengths in terms of therapist skills when working with this group. Method: Fifty therapists attending a training event completed a survey about their experience of adapting CBT for autistic clients, alongside a measure of therapist confidence. Results: Almost all therapists reported making adaptations to CBT practice when working with autistic clients. Key challenges identified were rigidity in thinking and pacing sessions appropriately. Therapists were relatively confident about core engagement and assessment skills but reported less confidence in using their knowledge to help this group. Therapist confidence was not associated with years of practice or number of adaptations made, but was positively associated with level of therapy training received. Conclusions: This study highlights a need for training and ongoing supervision to increase therapist confidence in and ability to make appropriate adaptations to CBT treatment protocols for autistic people.